2002
DOI: 10.1182/blood.v99.2.627
|View full text |Cite
|
Sign up to set email alerts
|

Neoplastic T cells in angioimmunoblastic T-cell lymphoma express CD10

Abstract: Angioimmunoblastic T-cell lymphoma (AITL) is a systemic disease involving lymph nodes, spleen, and bone marrow. Although the histologic features have been well described, the diagnosis is often challenging, as there are no specific phenotypic or molecular markers available. This study shows that the neoplas-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

21
277
9
10

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 316 publications
(317 citation statements)
references
References 27 publications
21
277
9
10
Order By: Relevance
“…3 In early lymph node involvement by angioimmunoblastic T-cell lymphoma, the neoplastic T cells preferentially occupy the B-cell follicles and immediate perifollicular area, suggesting that the follicle center microenvironment plays a role in tumor development. 2,4,5 The expression of CXCL13 by angioimmunoblastic T-cell lymphoma, as documented in our recent publication, 6 provides another piece of evidence linking the tumor cells to germinal center T-helper cells. CXCL13, a chemokine critical for B cell entry into germinal centers, 7 was identified by Kim et al 8 as one of the most highly upregulated genes in the germinal center T-helper cell subset.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…3 In early lymph node involvement by angioimmunoblastic T-cell lymphoma, the neoplastic T cells preferentially occupy the B-cell follicles and immediate perifollicular area, suggesting that the follicle center microenvironment plays a role in tumor development. 2,4,5 The expression of CXCL13 by angioimmunoblastic T-cell lymphoma, as documented in our recent publication, 6 provides another piece of evidence linking the tumor cells to germinal center T-helper cells. CXCL13, a chemokine critical for B cell entry into germinal centers, 7 was identified by Kim et al 8 as one of the most highly upregulated genes in the germinal center T-helper cell subset.…”
mentioning
confidence: 75%
“…Recent studies have suggested that a defining feature of angioimmunoblastic T-cell lymphoma may be its origin from germinal center T-helper cells. [2][3][4] Typically, the tumor cells of angioimmunoblastic T-cell lymphoma have a Thelper cell phenotype expressing CD3, CD4 and frequently CD10, similar to a subset of normal germinal center T-helper cells. 3 In early lymph node involvement by angioimmunoblastic T-cell lymphoma, the neoplastic T cells preferentially occupy the B-cell follicles and immediate perifollicular area, suggesting that the follicle center microenvironment plays a role in tumor development.…”
mentioning
confidence: 99%
“…CD10 expression is seen in roughly 70% of angioimmunoblastic T-cell lymphoma cases and although useful for detecting angioimmunoblastic T-cell lymphoma in most non-nodal sites, it has less utility in skin biopsies. 27,41,42,43,56 We do not know exactly the percentage of mycosis fungoides cases that are CD10( þ ) but based on our flow cytometry data, roughly 16.7% (6/36) of mycosis fungoides cases were found to express CD10. An evaluation of a large number of mycosis fungoides cases for follicular center helper T-cell markers including CD10 and Bcl-6 would be necessary to determine more precisely the frequency of reactivity of these markers and their relationship to one another and, ultimately, their utility in distinguishing mycosis fungoides from angioimmunoblastic T-cell lymphoma.…”
Section: Discussionmentioning
confidence: 81%
“…15,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] These include angioimmunoblastic T-cell lymphoma, peripheral T-cell lymphoma with a follicular growth pattern, primary cutaneous CD4( þ ) small/ medium-sized pleomorphic T-cell lymphoma and, occasionally, peripheral T-cell lymphoma, not otherwise specified and anaplastic large cell lymphoma. 15,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Clinically, primary cutaneous CD4( þ ) small/ medium-sized pleomorphic T-cell lymphoma and angioimmunoblastic T-cell lymphoma present or may present with primary cutaneous involvement. 20,[36][37][38][39][40] Other CD4( þ ) T-cell lymphomas with primary cutaneous manifestations include mycosis fungoides and its variants including Sezary syndrome, adult T-cell leukemia/lymphoma and primary cutaneous CD30 þ lymphoproliferative disorders.…”
mentioning
confidence: 99%
See 1 more Smart Citation